Osmotic Dehydration of Banana (Dwarf Cavendish) Slices - Kar, Abhijit; Chandra, Pitam; Prasad, Rajender; Samuel, DVK; Khurdiya, D S (Journal of Agricultural Engineering, 2001)
Osmotic dehydration Of banana slices (Dwarf Cavendish) was studied at five levels each of temperature 25°C, 35°C, 45°C, 55°C and 65°C, solution to sample ratio 1, 3, 5, 7 and 9; and concentration of sugar solution 40, 50, 60, 70 and 80° Brix. A modified second order rotatable design was adopted for three factors each at five levels. The moisture loss and sugar gain were characterized at one-hour interval for four hours. Response Surface Methodology was used to optimize the osmotic dehydration with special reference to maximum moisture remoyal and minimum solids gain. The study indicated that about 16% of the initial moisture could be removed from the banana slices after one hour of osmosis at a sugar concentration 70° Brix, solution to sample ratio of 1.5 and a temperature of 50°C with only 5% of initial solids as sugar gain. The second order response surface model could estimate the moisture losses as well as solids gain within 5% of the observed value.